2016
DOI: 10.1016/j.conbuildmat.2016.08.085
|View full text |Cite
|
Sign up to set email alerts
|

The role and interaction of superplasticizer and emulsifier in fresh cement asphalt emulsion paste through rheology study

Abstract: The workability and mechanical properties of cement asphalt emulsion (CA) mortar are unstable due to the complex interaction between cement and asphalt emulsion. To reveal the interaction between cement and asphalt emulsion, the effect of emulsifier and superplasticizer on the rheology of cement paste and asphalt emulsion is investigated, respectively, and the effect of the interaction between emulsifier and superplasticizer on the rheology of cement paste is studied in this paper as well. Results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Therefore, the anionic asphalt emulsion could only exert some slight hindrances to the hydration of C3S and C2S. As it is the hydration of C3S and C2S that mainly contributes to the strength development of PC paste, it could be deduced that anionic asphalt emulsion is more suitable than cationic asphalt emulsion for formulating CA mortars when a higher strength is required (such as the Type II CA Mortar as specified in the current Chinese Standard) [17][18][19]. However, the effect of anionic asphalt emulsion on the hydration of -3-PC has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the anionic asphalt emulsion could only exert some slight hindrances to the hydration of C3S and C2S. As it is the hydration of C3S and C2S that mainly contributes to the strength development of PC paste, it could be deduced that anionic asphalt emulsion is more suitable than cationic asphalt emulsion for formulating CA mortars when a higher strength is required (such as the Type II CA Mortar as specified in the current Chinese Standard) [17][18][19]. However, the effect of anionic asphalt emulsion on the hydration of -3-PC has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results indicate that the response of the electrical resistance of composites with SDBS to external force is more stable and sensitive than that of composites with Sodium dodecyl sulfate. Ouyang et al (2016) studied the effect of emulsifier and superplasticizer on the rheology of cement paste and asphalt emulsion and the results show that the apparent viscosity and yield stress of asphalt emulsion increase with superplasticizer and emulsifier dosage. Wang et al (2018) synthesized a new cationic surfactant containing non-ionic aliphatic alcohol polyoxyethylene ether using epichlorohydrin, octadecyl dimethylamine, and aliphatic alcohol polyoxyethylene ether as raw materials.…”
Section: Emulsifier and Emulsified Asphaltmentioning
confidence: 99%
“…Another aspect that must be considered when several chemical admixtures are simultaneously used in the formulation of the same cement paste is its synergic effect [62][63][64][65]. For example, it was observed that a polysaccharide viscosity-modifying agent (Welan Gum) has a higher influence on rheological properties of cement pastes formulated with an ester polycarboxylate superplasticizer than when it was formulated with an ether polycarboxylate [66].…”
Section: Chemical Admixtures Influencementioning
confidence: 99%